The Effect of Lecture Method Counseling on Knowledge and Attitudes of Couples of Childbearing Age (EFA) About Tubectomy Contraceptive Devices in Tontonunu District, Bombana Regency - Rai Adiana M, I Made (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Tubectomy is one of the best and most effective methods of contraception for women who have problems with the use of hormonal and non-hormonal contraceptive methods. The low use of tubectomy contraception is one of them related to knowledge and attitudes. The purpose of this study was to determine the effect of counseling with the lecture method on the knowledge and attitudes of couples of childbearing age about tubectomy contraception in the District of Tontonunu, District of Bombana. This type of research is Experimental with a static group comparison design. The research population is couples of childbearing age aged 15-49 years. The number of samples is 50 respondents. Sampling technique with random sampling system. Collecting data by using a questionnaire. Data analysis using Paired Sample t-Test. The results showed that there was an effect of giving counseling using the lecture method on knowledge (average increase of 83.00) and attitude (average increase of 74.00). Conclusion; there is an effect of providing counseling with the lecture method on the knowledge and attitudes of EFA about tubectomy contraception. Suggestion; The need for health education by using other methods to determine whether there is an effect of these methods.